2017
DOI: 10.1128/jvi.00880-17
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus NS5A Targets Nucleosome Assembly Protein NAP1L1 To Control the Innate Cellular Response

Abstract: (HCV) is a single-stranded positive-sense RNA hepatotropic virus. Despite cellular defenses, HCV is able to replicate in hepatocytes and to establish a chronic infection that could lead to severe complications and hepatocellular carcinoma. An important player in subverting the host response to HCV infection is the viral nonstructural protein NS5A, which, in addition to its role in replication and assembly, targets several pathways involved in the cellular response to viral infection. Several unbiased screens i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 84 publications
2
21
1
Order By: Relevance
“…According to a recent study, depletion of NAP1L1 in hepatocytes leads to the down‐regulation of 358 genes, and Ingenuity Pathway Analysis of the downregulated genes indicates that PI3K/AKT signaling is one of the top canonical pathways. GAB1, an important upstream regulator of PI3K/AKT/mTOR, is among those downregulated genes . We therefore speculated that NAP1L1 might activate PI3K/AKT/mTOR signaling through GAB1.…”
Section: Resultsmentioning
confidence: 98%
“…According to a recent study, depletion of NAP1L1 in hepatocytes leads to the down‐regulation of 358 genes, and Ingenuity Pathway Analysis of the downregulated genes indicates that PI3K/AKT signaling is one of the top canonical pathways. GAB1, an important upstream regulator of PI3K/AKT/mTOR, is among those downregulated genes . We therefore speculated that NAP1L1 might activate PI3K/AKT/mTOR signaling through GAB1.…”
Section: Resultsmentioning
confidence: 98%
“…Despite this methodological limitation, the list of NAP1L1 functions is continuously growing. Recent studies have demonstrated interaction of NAP1L1 with the intrinsically disordered, carboxy-terminal fragment of HCV NS5A protein (61). However, the data about the role of this interaction in HCV biology are somewhat contradictory (61,62).…”
Section: Fig 11mentioning
confidence: 99%
“…It has also been demonstrated that HCV is able to induce PKR phosphorylation, activating its kinase function and inhibiting antiviral effector translation [84,86,87]. Recently, NS5A was also reported to interact with the nucleosome assembly protein 1-like 1 (NAP1L1), a nuclear-cytoplasmic chaperone reported to be involved in the regulation of several host pathways, such as transcription or cell cycle progression [91]. In HCV-genotype 2 infection, NS5A-NAP1L1 interaction results in the sequestration of NAP1L1, inducing its proteasomal degradation and impeding its nuclear translocation.…”
Section: Ns5a and E2mentioning
confidence: 99%
“…In HCV-genotype 2 infection, NS5A-NAP1L1 interaction results in the sequestration of NAP1L1, inducing its proteasomal degradation and impeding its nuclear translocation. NAP1L1 targeting downregulates the transcription of several genes essential for innate immunity, such as RIG-I-and TLR3-mediated responses [91]. Moreover, it has been shown that NS5A downregulates type I and type III IFNs activation induced by RIG-I-and MDA5-mediated responses.…”
Section: Ns5a and E2mentioning
confidence: 99%
See 1 more Smart Citation